Results of a modified posterolateral approach for the isolated posterolateral tibial plateau fracture - Liu, Guan-Yi (Indian J Orthop, 2016)
BACKGROUND: There are few posterolateral approaches that do not require the common peroneal nerve (CPN) dissection. With the nerve exposure, it would pose a great challenge and sometimes iatrogenic damage over the surgical course. The purpose was to present a case series of patients with posterolateral tibial plateau fractures treated by direct exposure and plate fixation through a modified posterolateral approach without exposing the common peroneal nerve (CPN). MATERIALS AND METHODS: 9 consecutive cases of isolated posterior fractures of the posterolateral tibial plateau were operated by open reduction and plate fixation through the modified posterolateral approach without exposing the CPN between June 2009 and January 2012. Articular reduction quality was assessment according to the immediate postoperative radiographs. At 24 month followup, all patients had radiographs and were asked to complete a validated outcome measure and the modified Hospital for Special Surgery (HSS) Knee Scale. RESULTS: All patients were followedup, with a mean period of 29 months (range 25–40 months). Bony union was achieved in all patients. In six cases, the reduction was graded as best and in three cases the reduction was graded as middle according to the immediate postoperative radiographs by the rank order system. The average range of motion arc was 127° (range 110°–134°) and the mean postoperative HSS was 93 (range 85–97) at 24 months followup. None of the patients sustained neurovascular complication. CONCLUSIONS: The modified posterolateral approach through a long skin incision without exposing the CPN could help to expand the surgical options for an optimal treatment of this kind of fracture, and plating of posterolateral tibial plateau fractures would result in restoration and maintenance of alignment. This approach demands precise knowledge of the anatomic structures of this region.